Penguasaan Kosakata dalam Pembelajaran BIPA Melalui Kata Serapan dalam Bahasa Indonesia - Ratino Ratino; Laily Nurlina (Universitas Maritim AMNI Semarang, 2025)
This research aims to examine the use of loan words as teaching material for Indonesian Language for Foreign Speakers (BIPA) in mastering vocabulary. This research is motivated by the development of the Indonesian language, one of the processes of which is through loanwords. Data was obtained from various sources such as scientific journals, books and relevant articles. Data analysis was carried out qualitatively with a focus on identifying main themes, patterns and relationships between various variables in the literature that had been collected. The results of the research show that loan words can be used as BIPA teaching materials which are useful for facilitating understanding and enriching vocabulary for BIPA learners. Loan words originating from various languages such as Arabic, Dutch, English, Sanskrit, Portuguese, French, Chinese, Japanese, Persian, Greek, Hindi and others are proof that Indonesian is adaptive and open to other languages. The strategies used for BIPA learning using loanwords include cognitive approaches, use in daily conversations, introduction to grammatical concepts, and approaches to daily contexts, academic use, and use in the field of technology.